PKM PENANAMAN BIBIT KACANG PANJANG DI DESA TANI BHAKTI SAMBOJA BARAT KUTAI KARTANEGARA - Dwi Taufik Rohman; Cinta Amalia; Febi Ghalsananda; Ghea Asya Hermanita; Intan Cahyani Sari; Rafli Ocis Alexsandro Latupeirissa (Jurnal Abdimas Bina Bangsa, 2023)
Tani Bhakti Village, West Samboja District, Kutai Kartanegara Regency, is a village with a large number of people working as farmers and ranchers. Therefore, there are various agriculture and plantations in Bhakti Tani Village. In accordance with the theme of Balikpapan University's Real Work Lecture XIII, which is "Strengthening Food Security" there is an opportunity to further improve agriculture in the village. In addition, with a lot of knowledge from the community in Tani Bhakti Village, it is very helpful to plant long bean seeds because the success rate is very high. Long beans also don't need extra effort to grow them only need precision to make the fertilizer so that seeds that have grown into long beans can creep up. After KKN, the surrounding community also intends to continue planting long beans to increase and increase agriculture in Bhakti Tani Village